Гарантия качества образования: монография - Круглов В. И. Виктор Иванович; Азарьева В. В. Вера Владимировна; Горленко О. А. Олег Александрович; Мирошников В. В. Вячеслав Васильевич; Борбаць Н. М. Николай Михайлович; Можаева Т. П. Татьяна Петровна (Старый Оскол, ТНТ, 2022)
Авт. указаны на обл.